Eficiência do uso de nutrientes em sistemas de aléias na periferia da Amazônia - Serpa, Sheilla Silva e (2011)
In the SE periphery of Brazilian Amazonia, low-input agriculture systems on sandy loam soils have very low nutrient use efficiency. In a low-input alley cropping system, we measured residue decomposition dynamics and the yield and nutrient uptake of a maize crop associated with the following treatments: Clitoria+Pigeon pea; Acacia+Pigeon pea; Leucaena+Clitoria; Leucaena+Acacia, Leucaena+Pigeon pea and no residue input (control). The acacia treatments provided better soil coverage throughout the whole corn cycle. Potassium was released faster than nitrogen from the residues; N concentration in corn leaves in the residue treatments were below critical levels. The Leucaena+Acacia treatment was the most effective in increasing post-tasseling N and K assimilation and K use efficiency. This resulted in corn productivity 3.5 times greater (7.3 Mg ha-1) than the control without residue application. In the Amazonian sandy loam soils, which are susceptible to hardsetting and nutrient leaching, efficient N and K use should be priorities for soil management. Although no-till alley cropping of leguminous trees constitutes an important option for low-input farming, its efficiency depends on using a mixture of residues that keeps soil covered and have high rates of both N and K release during the entire crop cycle